Programmable cell stretcher - Huang, Yuli. (2013)
In the recent decades, it has become widely known that the physiological changes in cells can be induced by various mechanical stimuli. The study of mechanobiology is established at the end of the last century to investigate the cell response to mechanical stimulus. Detailed understanding of this causality enables the discovery of new mechanical-based therapies and new drugs that specially targets at the mechanotransduction signalling pathways. Driven by this vast biomedical potential, various mechanisms with the capability of applying different types of physical stimulus to cells in vitro have emerged. One of the most popularly studied stimuli is cyclic tensile strain, which exists ubiquitously in human native tissues and is proven to have up-regulatory effects to most of the cell activities.